Adaptive Governance dalam Pendistribusian Bansos oleh Dinas Sosial Pasca Bencana Banjir Lahar Dingin di Kabupaten Tanah Datar - Nabila Afifah; Rahmadhona Fitri Helmi (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2025)
West Sumatra Province, particularly Tanah Datar Regency, is one of Indonesia’s disaster-prone regions, recently affected by a cold lahar flood triggered by the volcanic activity of Mount Marapi. This disaster caused severe infrastructure damage and fatalities, posing significant challenges to the effectiveness of social aid distribution under emergency conditions. This study aims to analyze the implementation of adaptive governance principles in the distribution of social assistance by the Social Affairs Office of Tanah Datar Regency, focusing on four main pillars: collaboration, coordination, social capital development, and capacity building. A qualitative descriptive method was employed, involving in-depth interviews, field observations, and documentation of 15 key informants from various stakeholders. The findings reveal that collaborative and coordinative practices have been functionally applied but remain largely informal and undocumented within a systematic framework. Community social capital played a critical role in supporting aid distribution, though it has yet to be fully institutionalized. Meanwhile, institutional and human resource capacity faces limitations, particularly in the use of information technology and preparedness for large-scale disasters. The study concludes that the application of adaptive governance in disaster management requires strengthened coordination structures, real-time information systems, and active community engagement across all governance processes. This research contributes both theoretically and practically to developing a more resilient, inclusive, and responsive model for post-disaster social aid distribution.